A Hinduism of their Own: Emerging Guyanese Hindu Reading Practices in New York City. (14th October 2020) - Pillai, Rupa
Abstract: Immigrating to New York City presents new issues for Indo–Guyanese, especially as many find themselves in lower class positions while navigating a racial structure distinct from Guyana. A subset of these Indo–Guyanese Americans, particularly middle class women as well as the 1.5– and second generation, believes Guyanese Hinduism, the forms of Hinduism adapted to the Guyanese context, must adapt again to continue to be relevant to the community in their new home. Central to their call is questioning the religious authority of pandits. As I will discuss, pandits occupy a powerful position in Guyanese Hindu community that extends beyond the religious sphere. The key to their authority lies in their ability and skill to read and interpret Hindu scripture. However, I argue the realities of migration have resulted in a questioning of religious authority and how pandits read these texts. With some Guyanese Hindus uncertain of the reliability of their pandit's reading of scriptural text, there is a desire to engage in a Hinduism untainted by the biases of pandits. The presumed truth held within Hindu scripture has inspired some devotees to return to the text or rather to engage the text on their own for the first time. As a result, new reading practices are appearing within the community, which encourages Guyanese Hindus to craft a Hinduism that will serve them.